The Influence of Financial Literacy, Risk Perception, and Religiosity on Investment Decision in Islamic Financial Products - Noor, Aris Setia (International Journal of Business, Law, and Education, 2025)
This study investigates the influence of Financial Literacy, Risk Perception, and Religiosity on Investment Decision in Islamic financial products. A structural equation modeling approach using SmartPLS was applied to a sample of individuals who are potential investors in Islamic financial products. The results indicate that Financial Literacy and Religiosity have a significant positive impact on investment decisions, with Religiosity showing the strongest influence. Risk Perception also significantly affects investment decisions, although to a lesser extent. The model explains 54.2% of the variance in Investment Decision, with a Q² value of 0.387, suggesting good predictive relevance. These findings highlight the importance of enhancing financial literacy programs and addressing religious considerations to promote investment in Islamic financial products. The study contributes to the understanding of how personal and religious factors influence investment behavior in the context of Islamic finance.